PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN ILMU PENGETAHUAN SOSIAL MATERI KONFLIK SOSIAL SISWA KELAS VIII SMP NEGERI 1 PASURUAN TAHUN PELAJARAN 2023/2024 - Said Padli, Muhamad; Danil Wathoni, Muh; Kurniawati, Aida; Fauziah, Neneng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the improvement in learning outcomes in social studies subjects on social conflict material for class VIIIC students at SMP Negeri 1 Pasuruan for the 2023/2024 academic year by implementing the Quiz Team type active learning strategy. This research was conducted using the Classroom Action Research method which involved 32 people, 14 male and 18 female class VIII students as research subjects. The research results show that the application of a quiz team type active learning strategy can improve student learning outcomes. The average value of student learning outcomes increased from 64.41% in the sufficient category, increasing in the first cycle to 34.3% of students who achieved the KKM with an average percentage of students' social studies learning outcomes of 68.75% in the sufficient category. After implementing corrective actions in cycle II, the number of students who achieved the KKM increased to 75% with the average percentage of students' social studies learning outcomes increasing to 83.13% and being in the good category. The conclusion obtained from this research is that the quiz team type active learning strategy can be an effective alternative in improving student learning outcomes in social studies social conflict subjects.